Proteção de dados e dimensões do poder: o direito na era do capitalismo de vigilância - Sutel, Roberta de Oliveira (2024)
This dissertation is part of the Social Relations and Dimensions of Power concentration area of ​​the Postgraduate Program of the University of Passo Fundo-RS. The work aims to analyze the behavior of law in the face of surveillance capitalism and to question how the new form of power that has emerged in this current capitalism relates to legal protection. To respond to the problem, it uses the deductive approach method and the monographic procedure method. The main hypothesis is that capitalism is a system in constant change, which implies that the practices of collecting and using personal data are also in constant evolution. In the first part, the work deals with the historical context of data protection in Brazil, until culminating in the enactment of the General Data Protection Law, including examples of incidents involving private entities and public administration. In the second section, the paper addresses issues of power, where surveillance capitalism is inserted into other dimensions of power, occupying the top of a pyramid. In the third and final chapter, the paper offers a counterpoint to legal protection and then concludes that the relationship between surveillance capitalism and legal protection is not limited to the implementation of regulations, but also encompasses complementary approaches such as the promotion of digital education and awareness of online privacy and security issues. These approaches complement legislation, especially the General Data Protection Law, and are fundamental to dealing with the dilemmas that arise as a result of surveillance capitalism.